[Cs6Cl][Fe24Se26]: A Host–Guest Compound with Unique Fe–Se Topology. Issue 13 (16th February 2016) - Valldor, Martin; Böhme, Bodo; Prots, Yurii; Borrmann, Horst; Adler, Peter; Schnelle, Walter; Watier, Yves; Kuo, Chang Yang; Pi, Tun‐Wen; Hu, Zhiwei; Felser, Claudia; Tjeng, Liu Hao
Abstract: The novel host–guest compound [Cs6 Cl][Fe24 Se26 ] ( I 4/ mmm ; a =11.0991(9), c =22.143(2) Å) was obtained by reacting Cs2 Se, CsCl, Fe, and Se in closed ampoules. This is the first member of a family of compounds with unique Fe–Se topology, which consists of edge‐sharing, extended fused cubane [Fe8 Se6 Se8/3 ] blocks that host a guest complex ion, [Cs6 Cl] 5+ . Thus Fe is tetrahedrally coordinated and divalent with strong exchange couplings, which results in an ordered antiferromagnetic state below T N =221 K. At low temperatures, a distribution of hyperfine fields in the Mössbauer spectra suggests a structural distortion or a complex spin structure. With its strong Fe–Se covalency, the compound is close to electronic itinerancy and is, therefore, prone to exhibit tunable properties. Abstract : Fused cubane : A unique Fe–Se lattice (see figure) hosts the complex ion [Cs6 Cl] 5+ . Tetrahedrally coordinated magnetic Fe 2+ ions, found in separated octamers, order antiferromagnetically below T N =221 K. Spectroscopic data suggest that this host–guest compound is close to electronic itinerancy.